Effect of online quizzes on music theory achievement of freshman music teaching students - Hatice Çeliktaş; Rasim Erol Demirbatır (Intelektual Pustaka Media Utama, 2022)
This research examined the effects of online quizzes on the music theory achievement of freshman music teaching students. For this purpose, the students who took the Western Music Theory and Practice I course were determined as the study group and experimental research was conducted. A pre-assessment test was given to determine students’ knowledge level about music theory and the median value of the test was determined as the cut-off point. The cut-off point was established as the experimental group, while the cut-off point was established as the control group. In the semester, four online quizzes were given to the experimental group apart from the midterm and final exams. Finally, a final test was applied to whether there was a significant difference between the groups. Consequently, there was no significant difference between the two groups. However, it was seen that the experimental group scores are slightly higher than the control group scores, thus the experimental group achieved the success of the control group. When it was compared to the pre-assessment test scores, it shows that the students in the experimental group achieved a remarkable positive difference in the process. The discussion includes recommendations about the use of online quizzes.